Impact of Salinity Stress on Soybean Growth and Yield under Saturated Soil Culture in Tidal Lands: A Comparative Study of Tolerant Varieties - Nasution, Siti Nurminah; Ghulamahdi, Munif; Melati, Maya (Journal of Tropical Crop Science, 2024)
Salinity stress, intensified by climate change events such as El Niño and drought, presents a significant challenge to soybean production in tidal lands. This study evaluated soybean varieties’ growth, tolerance, and yield under varying salinity conditions within a saturated water cultivation system. The experiment was conducted from February to May 2024 at the IPB Experimental Station in Leuwikopo, Bogor, Indonesia, using soil samples collected from type B tidal lands in Mulyasari Village, Banyuasin, South Sumatra. A completely randomized design (CRD) was employed with three factors and three replications each. The first factor was soybean variety (“Demas-1” and “Detap-1”), the second was soil salinity (0 and 2000 ppm NaCl), and the third was irrigation salinity at different growth stages (control, 2000 ppm NaCl before/during flowering, and 2000 ppm NaCl after flowering). The results demonstrated that the “Demas-1” variety exhibited superior growth characteristics, including higher leaf greenness, dry weight of root nodules, and number of filled pods per plant. Exposure to soil salinity of 2000 ppm NaCl led to a significant reduction in plant height (29.38%), leaf number (38.01%), leaf greenness (28.67%), dry weight (49.90%-60.80%), and filled pods per plant (55.51%), while increasing plant toxicity (108%). Irrigation with 2000 ppm NaCl further exacerbated these negative impacts, resulting in decreased leaf greenness (15.42%-18.06%) and filled pods per plant (17.84%-23.94%). The interaction between soybean variety, soil salinity, and irrigation salinity significantly influenced the number of filled pods per plant. The combination of any soybean variety with 2000 ppm NaCl resulted in a reduction of filled pods per plant. Moreover, applying saline irrigation after flowering to saline soil decreased the number of filled pods per plant by 64.68%. These findings highlight the critical importance of selecting tolerant soybean varieties and implementing effective irrigation management strategies to mitigate the adverse effects of salinity on soybean production in tidal lands.